Evaluation of Effects of Credit-Risk on Return on Assets of Commercial Banks in Nepal - Dr. Kapil Khanal, (Journal of Balkumari College, 2022)
Introduction: The major cause of bank distress in Nepal is associated with poor credit management which results to decline in credit standing of the banks. The study adopts judgmental sampling techniques. Objective: To analyze and evaluate the impact of credit-risk ratio on return on assets of commercial banks in Nepal. Research design: Descriptive and exploratory research designs were used. Methods and materials: Review of various articles and collection of secondary data through the websites of Nepal Rastra Bank. Results and conclusion: It is found that there is inverse relationship between credit risk ratio and return on assets ratio. The findings provide sufficient evidence that credit risk management indicators impact significantly on commercial bank performance in Nepal. Article type: Research Paper